2003
DOI: 10.1086/379387
|View full text |Cite
|
Sign up to set email alerts
|

A Woman Down to Her Bones

Abstract: Based on a wide range of Latin and vernacular sources, this essay reexamines Thomas Laqueur's and Londa Schiebinger's influential claim that the idea of incommensurable anatomical difference between the sexes was "invented" in the eighteenth century, reflecting, in particular, a need to resort to nature in order to justify female subordination against new ideals of equality and universal rights. It provides ample evidence that already around 1600 many leading physicians, rather than proclaiming a "one-sex mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(10 citation statements)
references
References 11 publications
0
5
0
5
Order By: Relevance
“…In the last few decades, historians of gender and sexuality have objected that Laqueur's two‐stages narrative is built upon scarce and biased sources, and simplifies a much more nonlinear and complex history in which the themes of sameness and difference between the sexes cohabited in different time periods (Harvey, 2002 ; King, 2013 ; Linton, 2022 ; Stolberg, 2003 ). 1 Importantly for the case of the female orgasm, Alison Moore ( 2018 ) has convincingly shown that two different versions of the homologous model cohabited well into the 19th century.…”
Section: Erotic Homology and Reproductive Homology In Pre‐evolutionar...mentioning
confidence: 99%
“…In the last few decades, historians of gender and sexuality have objected that Laqueur's two‐stages narrative is built upon scarce and biased sources, and simplifies a much more nonlinear and complex history in which the themes of sameness and difference between the sexes cohabited in different time periods (Harvey, 2002 ; King, 2013 ; Linton, 2022 ; Stolberg, 2003 ). 1 Importantly for the case of the female orgasm, Alison Moore ( 2018 ) has convincingly shown that two different versions of the homologous model cohabited well into the 19th century.…”
Section: Erotic Homology and Reproductive Homology In Pre‐evolutionar...mentioning
confidence: 99%
“…In der medizinhistorischen Literatur ist umstritten, wann genau (die meisten Autoren tendieren auf die Mitte bis das Ende des 18. Jahrhunderts) sich das zweigeschlechtliche dichotome Modell (nach Aristoteles) der Geschlechter gegenüber dem hippokratisch-galenischen mischgeschlechtlichen Modell durchsetzte [ 16 , 17 ].…”
Section: Re-review Zuunclassified
“…26 If this was indeed the case, Laqueur's argument that the two-sex model was invented because it suited enlightened thinkers who wished to justify the subordination of women, cannot be sustained. In a very well researched article, Michael Stolberg has questioned the validity of this explanation by pointing to inconsistencies in the periodisation offered by Laqueur and Schiebinger.…”
Section: Social Constructivism Gender History and The One-sex/two-sementioning
confidence: 99%